THE LANGUAGE POLICY OF THE UKRAINIAN DIASPORA IN THE USA IN THE INFORMATION SUPPORT OF UKRAINIANS DURING THE PERIOD OF RUSSIAN AGGRESSION (2014-2024) - SHYNKARYK, Iuliana (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2024)
Abstract. The article highlights the processes of development of Ukrainian studies in the USA by the Ukrainian diaspora during 2014-2024. Attention is focused on functioning of Ukrainian schools, organization of language courses for studying Ukrainian language online, supporting of scientific centers and projects on Ukrainian themes, as well as establishing connections with Ukrainian institutions. The study, referring to numerous publications, proved the role of popularization the Ukrainian language in countering Russian informational and cultural aggression. Attention is drawn to the role of the diaspora in the elimination of Russian and Soviet colonial names, pseudo-scientific theories, etc. The reflections of Ukrainian scientists on the issue of orthography and the language policy of Ukraine in general have been analyzed. The role and achievements of Ukrainian scientists in the USA in the field of philology and history are emphasized. The conducted scientific research emphasizes that there is a demand for the Ukrainian language and culture in the world democratic society, and this is a unifying factor of national forces and needs to be developed and strengthened in the conditions of Russian war against Ukraine.